PENGARUH ROMBONGAN BELAJAR TERHADAP KOGNITIF SISWA DALAM MATA PELAJARAN MATEMATIKA DI SD NEGERI 01 MENTAWA TAHUN PELAJARAN 2023-2024 - Sabariah Sabariah; Eliyah, Mutazam (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This thesis discusses the Influence of Study Groups on Student Cognition in Mathematics Subjects at SDN 01 Mentawa for the 2023-2024 Academic Year. This study has three objectives, namely: 1) Describe students' cognition according to the standards of the study group in mathematics subjects at SDN 01 Mentawa for the 2023-2024 Academic Year. 2) Describe the cognition of students if they exceed the standards of the study group in mathematics subjects at SDN 01 Mentawa for the 2023-2024 Academic Year. 3) Determine the significant influence between the study group and students' cognition in mathematics subjects at SDN 01 Mentawa for the 2023- 2024 Academic Year. This study uses a quantitative approach and a type of comparative research with the secondary data analysis (ADS) research method. The data collection technique uses documentation. The data analysis technique uses validity tests, reliability tests, normality tests, and homogeneity tests. The results of the study showed that: 1. Cognitive results that were in accordance with the standards of the study group in mathematics subjects from the results of the SPSS analysis obtained a mean value or average value of PTS mathematics class III B of 58.92. The median value is 55. The value that often appears (mode) is 67. The range is obtained by subtracting the maximum and minimum values of 92 – 30 = 62. The total number of data is 1,650. 2. Cognitive results that exceeded the standard of the study group in mathematics subjects from the results of the SPSS analysis obtained a mean value or average score of PTS mathematics class III A of 55.13. The median value is 50. The value that often appears (mode) is 42. The range (data range) is obtained by subtracting the maximum and minimum values of 100 – 17 = 83. The total number of data is 1,654. 3. The results of the SPSS analysis obtained a value of Z = -0.885 and Sig./p = 0.376 > 0.05. Thus, it can be concluded that Ho was accepted and Ha was rejected. This means that there is no significant influence between the number of study groups that exceed the standard and those that meet the standards in mathematics subjects